2018
DOI: 10.5005/jp-journals-10006-1611
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cytology and its Correlation with Cervicovaginal Infection in Antenatal Patients: A Study in a Tertiary Care Hospital

Abstract: To study cervical cytology and cervicovaginal infection in antenatal women.Objectives: To find out by pap smear for inflammatory, atypical squamous cells of undetermined significance (ASCUS), atypical glandular cells of undetermined significance (AGUS) and premalignant lesions in antenatal women.• To find out cervicovaginal infection by wet mount among antenatal women.• Correlation of cervical cytology with cervicovaginal infection.Materials and methods: Five hundred antenatal women, irrespective of gestationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Among the 57 included studies, 22 (38.6%) described whether participants had reported symptoms and assessed symptom status. Of these 22 studies, 17 included participants with symptoms (14 reported the percentage of participants with symptoms) [ 24 , 29 , 39 , 42 , 43 , 45 – 47 , 58 , 59 , 65 , 67 , 69 , 77 79 , 84 ] and five studies included only participants without symptoms [ 55 – 57 , 70 , 82 , 83 ]. Reporting about symptom in terms of self-reported or clinician-observed symptoms and the level of detail varied between studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the 57 included studies, 22 (38.6%) described whether participants had reported symptoms and assessed symptom status. Of these 22 studies, 17 included participants with symptoms (14 reported the percentage of participants with symptoms) [ 24 , 29 , 39 , 42 , 43 , 45 – 47 , 58 , 59 , 65 , 67 , 69 , 77 79 , 84 ] and five studies included only participants without symptoms [ 55 – 57 , 70 , 82 , 83 ]. Reporting about symptom in terms of self-reported or clinician-observed symptoms and the level of detail varied between studies.…”
Section: Resultsmentioning
confidence: 99%
“…Reporting about symptom in terms of self-reported or clinician-observed symptoms and the level of detail varied between studies. Of the 22 studies, eight studies reported symptoms observed by the clinician [ 42 , 45 , 46 , 54 , 59 , 67 , 69 , 77 ], two only self-reported [ 43 , 78 ], five studies both [ 29 , 58 , 65 , 79 , 82 ] and seven did not reported if the symptoms were self-reported or clinician-observed [ 24 , 39 , 47 , 55 – 57 , 70 , 83 ]. Of the 17 studies which included participants with symptoms, six studies report proportions of different types of vaginal discharge and other symptoms which are associated with genital tract infections [ 29 , 43 , 47 , 54 , 65 , 67 ], ten reported if symptoms from a defined group of symptoms were present or absent [ 24 , 39 , 42 , 45 , 58 , 59 , 69 , 77 79 ], one did not report the type or definition of symptoms [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations